Brentwood Engaging Neighbours Report & Map ... - Josephson, Ken (University of Victoria Libraries, 2021)
A map showing cultural, heritage, and arts sites alongside sustainable and active living and community sites. Reverse of map features information about Brentwood Bay; a WSANEC (the local First Nations' term for the region of Saanich) Creation Story by John Elliott; a list of community resources; and information on the Community Tables: Engaging Neighbours initiative and its findings. This map is part of the Green Map System. ...